Use of Quercus ilex subsp. ballota phenological and pollen-production data for interpreting Quercus pollen curves (Aerobiologia, 2007)
Although aerobiological data are often used in phenological research as an indicator of ﬂowering, airborne pollen concentrations are inﬂuenced by a number of factors that could affect pollen curves. This paper reports on a study of various aspects of reproductive biology in Q. ilex subsp. ballota, together with environmental factors inﬂuencing pollen release and transport, with a view of achieving reliable interpretation of Quercus pollen curves in Ourense (NW Spain). Aerobiological data were recorded from 2002 to 2004 at two sites in the province of Ourense. From 1st February to the end of the ﬂowering period, phenological observations were carried out on 19 trees from the Q. ilex subsp. ballota population found in the Ourense area. Pollen production was calculated for the same trees. The chilling and heating requirements for triggering development were also calculated. The mean ﬂowering period lasted 11-15 days. Reduced pollen output per catkin and, especially, a reduced number of catkins per tree in 2003 and 2004, prompted a marked decline in overall pollen production. Major differences observed in Q. ilex subsp. ballota pollen curves were attributed to the considerable inﬂuence both of weather conditions during pollination and pollen production. In years with high pollen production and weather conditions favouring pollen release, Q. ilex subsp. ballota contributed almost 10% to the total Quercus pollen curve. Around 20% of the pollen trapped was captured before or after ﬂowering periods.